Meadow Falls [large type] - Brown, Carolyn, 1948- (Center Point Large Print, 2024)
"Angela Marie has spent all of her thirty-five years on Meadow Falls, the farm that's been in her Texas family for generations. It wasn't her plan. It was an obligation. Now that her parents -- less loving kin than strangers -- have passed, the whole shebang belongs to Angela. And a legacy she never wanted is hers to uphold. She can't forsake it now. Her beloved nanny, Mandy, who was always more of a mother, needs a caregiver herself. And Mandy's great-granddaughter, as close to Angela as a sister, has returned to roost. When a handsome veteran arrives seeking work as a farmhand, Angela thinks the future might not be half-bad after all. But it's the past that proves enlightening. Mandy is revealing secrets Angela never knew about her parents. As the clouds on her family history begin to part, the inheritance feels more like a precious gift, and Meadow Falls more like the home Angela's been looking for her whole life."--